2022
DOI: 10.3390/ijms23020996
|View full text |Cite
|
Sign up to set email alerts
|

Deranged Myocardial Fatty Acid Metabolism in Heart Failure

Abstract: The heart requires fatty acids to maintain its activity. Various mechanisms regulate myocardial fatty acid metabolism, such as energy production using fatty acids as fuel, for which it is known that coordinated control of fatty acid uptake, β-oxidation, and mitochondrial oxidative phosphorylation steps are important for efficient adenosine triphosphate (ATP) production without unwanted side effects. The fatty acids taken up by cardiomyocytes are not only used as substrates for energy production but also for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 143 publications
0
38
0
Order By: Relevance
“…PPARα-knockout mice have been shown to have a reduced rate of fatty acid oxidation. Interestingly, over-expression of cardiac-specific PPARα significantly reduced enzymes involved in mitochondrial oxidative phosphorylation [43][44][45].…”
Section: Discussionmentioning
confidence: 99%
“…PPARα-knockout mice have been shown to have a reduced rate of fatty acid oxidation. Interestingly, over-expression of cardiac-specific PPARα significantly reduced enzymes involved in mitochondrial oxidative phosphorylation [43][44][45].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple experimental animal and longitudinal studies have demonstrated that dietinduced obesity promotes pro-aging phenotypes [84,97,171,172]. A considerable component of the obesity-based drive of aging likely results in alterations in insulin sensitivity as well as the drive towards alternative sources of energy, such as lipid-or protein-mediated metabolism that can incur a greater level of oxidative stress [173][174][175].…”
Section: Obesity and Metabolic Dysfunctionmentioning
confidence: 99%
“…That estrogen-related receptor (which main productive molecules promoted by fatty Acyl-COAs productions) is known to regulate a wide range of gene expression in cardiomyocytes, including β-oxidation of FA, oxidative phosphorylation, and contractile proteins [59]. Also, Notes, the generation of Gp GTP subunits is imp for Acyl-COA synthesis (specifically the Gp GTP beta subunits) regulated by OPA1 enzymes in FOX pathway where decreasing in Acyl-COA-beta synthesis will reflect decreasing in both go GTP bêta sublime and in both PLCγ2 and IFN-beta synthesis that will reflect decreasing in the CMs and in ECs activities and functions through dropping in G-actin activities.…”
Section: So the Activation Of The Proper Rac1 In Non-muscle Myosin Lightmentioning
confidence: 99%